The Occurance of Depression in Older People using Social Care – Preliminary Results - Burzyńska, Monika; Maniecka-Bryła, Irena (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The purpose of this study was to assess the incidence of depression and factors determining its occurrence among beneficiaries of the City Social Care Centre Lodz-Polesie aged 65 and over. In conducting the study health related quality of life geriatric depression rating scale was used. The first stage of the research was conducted in 2011 among 108 people. In statistical analysis there were used: structure indices, measurable features distribution and χ2 test of independence. In the study there were 88 (81.5%) women and 20 (18.5%) men. The average age of beneficiaries was 78.2 years. Men receiving social care benefits were mainly bachelors or widowers, while women most often were widowed. Older people mainly benefited from the care services (77.1%). 22.9% of all patients benefited from financial assistance in the form of benefits. 81.2% of seniors indicated that they suffer from chronic diseases, while only 18.8% indicated that they are ill rarely or never. Among 78% of people probable depression was found. There was found statistic correlation between the incidence of depression and education, subjective assessment of health status and level of satisfaction with life. The most important conclusions are: 1) older people receiving social assistance are highly prone to depression, 2) understanding of the determinants of depression in the elderly can help to improve their quality of life and to reduce costs of medical aid caused this disease.